ASSESSMENT OF DRUM SEEDER ON DIRECT SEEDED RICE (ORYZA SATIVA) UNDER PUDDLED CONDITION - Singh, P.K.; Singh, R.N.; Singh, S.K.; KUMAR, BRAJESH; Singh, SANDIP K. (Annals of Agricultural Research, 2014)
A trail was carried out during the kharif season with the rice variety Raj. Mansuri. The trial consisted three treatments viz. conventational method (80 kg seed/ha+ handweeding at 30 and 45 days after planting +soil test based fertilizer dose ZnSO4 25 kg/ha broadcasting 100 kg (T1) seed/ha + hand weeding at 30 and 45 days after seeding + soil test based fertilizer dose + ZnSO4 25 kg/ha (T2) and seeding of 56 kg sprouted seed/ha with 12 row drum seeder two days after puddling +weed control through pretlachlor @ 0.5 kg ai/ha + soil test based fertilizer dose + ZnSO4 25 kg/h (T3).The highest grain and straw yield was recorded in T3 followed by T2 and T1, respectively. The highest net return was recorded with T3 followed by T1 during both the years. It may be due to higher grain yield and lower cost of cultivation. Use of 12 row drum seeder reduced expenditure on labour. Broadcasting recorded the lowest net return (Table 1).The highest benefit: cost ratio was recorded with T3 in both the years.